Settlement of the Criminal Action Damning of Good Name Through Electronic Media in the Polres of Ternate City - Mohtar Yusup; Rusdi Hasan; Abdul Wahab Hi. Anhar (Jurnal Geocivic, 2020)
This study aims to determine the settlement of criminal defamation cases through the electronic media of the Ternate City Police and to find out the considerations of the District Court Judges of Ternate in examining and deciding criminal defamation cases. The research method used is empirical normative with a descriptive research type. Sources of data consist of primary data, namely the results of interviews, and secondary data, namely primary, secondary, and tertiary legal data. Methods of data collection with literature study and interviews and then analyzed qualitatively. The results showed that the settlement of criminal defamation cases through electronic media at the District Police of Ternate in two ways, namely through penal means (repressive activities after the occurrence of a crime) and non-penal means, in the form of counseling for preventive action. The basis for consideration of the district court judges of Ternate in examining and deciding criminal defamation cases is based on formal considerations and material considerations. Based on the facts revealed at the trial, namely the fact that the defendant was found guilty of violating Article 27 paragraph 3 concerning the Law on Information and Electronic Transactions (UU ITE), and the act of defamation fulfilled the elements of Article 310 of the criminal code.